Afforestation and reforestation in the clean development mechanism of the Kyoto Protocol: implications for forests and forest people - Smith, J. (2002)
The social and environmental implications of plantations in the CDM are analysed under a hypothetical laissez faire approach and a proactive approach to sustainable development (SD), bounded by existing COP7 agreements and efficency and equity considerations. Implications for timber rich, timber depleted and inherently timber poor regions are assessed. The social risks of industrial plantations cannot fully addressed under COP7 rules and are likely to be highest in timber rich regions under repressive regimes or wherre politics dominate the forestry sector. Risk could, however, be reduced through minimum standards for stakeholder consultation and favourable legal institutions. Low cost opportunities with multiple benefits exist and require information dissemination, but some opportunities for biodiversity benefits will need financial support. Reduction of transaction costs would increase the participation of small holder plantations but their role is likely to remain limited. Inclusion of assisted natural regeneration opens up opportunities for options with multiple benefits.